Exercise economy in cross country skiing and running - Hallén, J.; Schäfer, D.; Losnegard, T. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Substantial inter-individual variations in exercise economy exist even in highly trained endurance athletes. The variation is believed to be partly determined by intrinsic factors. Therefore, we tested the hypothesis that the most economical subject in one exercise mode is also the most economical in other modes.